PERSEPSI SISWA SMP KELAS 7 TERHADAP KONSEP PEMANASAN GLOBAL - Yanti, Wahid Andri (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
This study aims to identify the perceptions and knowledge of students to the concept of global warming. Samples are junior high school students grade 7 were 58 students who were in Riau. Data obtained from open-ended questions posed to students. The results showed 18.96% of students give answers that are not related to the concept of global warming; 27.58% of students stated that global warming is emerging heat from the sun and the earth’s surface; 41.37% of students declared global warming is an increase in the average temperature of the earth; 5.2% of students stated that global warming associated with the depletion of the ozone layer; and 6.89% of students stated that global warming is the result of human activity. From these results it can be concluded that the students’ knowledge on environmental issues, especially global warming is low and the environmental education given has not been effective. Keywords: studentsâ€™ perception, global warming, environmental education.